Risk factors and diagnostic markers for Escherichia coli bloodstream infection in older patients. (March 2021) - Chen, Qiang; Ma, Guifeng; Cao, Huijun; Yang, Xiaoyu; Jiang, Yan
Highlights: Lithiasis and urinary infection are risk factors for bloodstream infection. Cephem use and drainage tube placement are associated with antibiotic resistance. Serum procalcitonin and neutrophil percentage have potential as diagnostic markers. Assessing these risk factors and markers may prevent bloodstream infection. Abstract: Objective: To investigate risk factors for Escherichia coli ( E. coli ) bloodstream infection (BSI) in older patients and the diagnostic accuracy of laboratory parameters. Methods: The electronic medical records of patients aged 60 years and above who were admitted with a serious condition were extracted. Propensity score matching (PSM) was used to ensure that the included patients had similar baseline clinical features. Multiple regression analysis was used to identify risk factors for E. coli BSI and extended-spectrum β-lactamase (ESBL)-producing E. coli BSI. Receiver operating characteristic (ROC) curve analysis was performed to determine the diagnostic utility of relevant laboratory indicators. Results: After PSM, 508 patients were included: 254 patients with E. coli BSI and 254 control patients. Bile duct stone (adjusted odds ratio [aOR] 5.131), kidney stone (aOR 3.678), and urinary system infection (aOR 3.173) were independent risk factors for E. coli BSI. Prior exposure to cephems (aOR 3.782) and drainage tube placement (aOR 2.572) were independent risk factors for ESBL-producing E. coli BSI. Serum procalcitonin (PCT) yielded the highest area under the curve (0.783) and the best cut-off value (1.3 ng/ml). Conclusion: Bile duct stone, kidney stone, and urinary system infection must be detected and treated early, in order to prevent E. coli BSI in older patients. Further, administration of cephems and invasive procedures must be undertaken with caution, in order to reduce the risk of BSI with ESBL-producing E. coli . Finally, serum PCT level has potential as diagnostic marker for E. coli BSI in older individuals.